Analisis Penerapan Metode Multivariate Analysis Of Covariance Dalam Jumlah Penumpang Mini Bus (Studi Kasus : CV. DR. Himpak Medan) - Winarti (Journal of Informatics, Electrical and Electronics Engineering, 2021)
In the current era of globalization and rapid economic development, means of transportation and communication are quite important needs, especially long and short distance transportation which have contributed the most to the needs of the community and government. The company CV.DR.HIMPAK Medan was given the task and authority to provide public transportation services for passengers and is a transportation vehicle that is much needed by people from all walks of life. The problem that often occurs in the world of transportation is the frequent occurrence of spikes or increases in passengers that can occur at any time, especially on important days such as Eid. For this reason, this research will create a system to predict the number of passengers using the Multivariate Analysis of Covariance method, which aims to make it easier to predict the number of passengers. This system helps CV.DR Himpak Medan so there is no more accumulation of passengers. For this reason, this research will create a system to predict the number of passengers using the Multivariate Analysis of Covariance method, which aims to make it easier to predict the number of passengers. with this system helps the parties CV.DR.Himpak Medan so that there is no more accumulation of passengers.